BABATURUNG SKOMBOR SEBAGAI METODE PENYEBARAN ISLAM DI KESULTANAN BACAN - Rustam Hasim (Jurnal GeoCivic, 2024)
The Bacan Sultanate was founded in 1322. Its first Sultan was Said Muhammad Bakir, or Said Husin, who ruled on Mount Makian with the title of Maharaja Who Reigns in the Kingdom of Moloku Astana Bacan, the Land of Komala Besi Lime Dolik. Like other sultanates in North Maluku, the Bacan sultanate, which grew and developed over a long period of time, had social stratification that was structured hierarchically. There are three social strata, of which there is only one main social stratum and the other two include the subjects of the sultanate.The culture of the Bacan Sultanate is full of religious activities, customs and art. One of the works or culture of the Bacan Sultanate that still exists today is babaturung skombor. Babaturung Skombor is a tradition of delivering and installing banners and curtains on the pulpit of the Sultan's mosque. This procession starts from the kedaton and then parades to the sultanate mosque on the 29th of Sha'ban and 28th of Ramadhan.This ritual has been carried out for generations in the Bacan sultanate. This procession starts from the palace of the Bacan Sultanate. In its implementation there are several stages. It starts with the assignment of traditional apparatus which is divided into two parts, namely World Bobato and Hereafter Bobato, each of which has a role in the procession